jsmetrics v0.2.0: a Python package for metrics and algorithms used to identify or characterise atmospheric jet streams - T. Keel; T. Keel; C. Brierley; T. Edwards (Geoscientific Model Development, 2024)
The underlying dynamics controlling jet streams are complex, but it is expected that they will have an observable response to changes in the larger climatic system. A growing divergence in regional surface warming trends across the planet, which has been both observed and projected since the start of the 20th century, has likely altered the thermodynamic relationships responsible for jet stream formation and control. Despite this, the exact movements and trends in the changes to the jet streams generally remain unclear and without consensus in the literature. The latest IPCC report highlighted that trends both within and between a variety of observational and modelling studies were inconsistent (Gulev et al., 2021; Lee et al., 2021). Trends in jet streams were associated with low to medium confidence, especially in the Northern Hemisphere.